Effects of condensed tannins from Leucaena leucocephala (Lam.) de Wit hybrid on population and cellulolytic activity of rumen fungi - Kok, Ching Mun (2012)
Condensed tannins (CT), which are secondary metabolites of Leucaena leucocephala, have both beneficial and harmful effects on ruminants. CT levels that do not exceed 5% dry matter (DM) could prevent bloat as well as provide bypass-protein to the animal. However, high levels of CT could reduce the nutritional value of Leucaena, decrease N digestibility and depress rumen digestion of fermentable carbohydrates. L. leucocephala hybrids, which are resistant to psyllid infestation, have been found to contain high CT levels and exhibited low digestibility in ruminant. It has been suggested that the low digestibility is attributed to the high CT content. However, it is not known whether the cellulolytic anaerobic rumen fungi, which play a major role in the digestion of fibrous feed materials, are affected by the CT from L. leucocephala hybrids. Thus, the objectives of this study were to determine the effects of a L. leucocephala hybrid (Bahru) containing high CT level on the population and cellulolytic activity of rumen fungi. The animals used in the study were eight Boer cross Saanen male goats. Four goats were randomly assigned to one of two diets: (i) control diet without L. leucocephala hybrid-Bahru and (ii) treatment diet containing 30% L. leucocephala hybrid-Bahru, which was equivalent to 1.8% CT of dietary DM. The goats were fed with 2.7% DM of mean body weight per day. The experiment was carried out twice using a cross over design and each experimental period was 30 days. Total rumen fungal population (expressed as fungal biomass) was estimated using real-time PCR. The results showed that the cellulolytic rumen fungal population of goats fed with L. leucocephala hybrid-Bahru decreased significantly at days 5 and 10 (12.38 µg/ml and 8.63 µg/ml), and then increased drastically at day 15 (157.00 µg/ml). However, the rapid growth was not sustained and the rumen fungal population decreased again at days 20 and 25 of feeding, and at day 30, the fungal population of treatment goats was not significantly different from that of the control goats. These results showed that growth of the cellulolytic rumen fungi was inhibited by the CT of L. leucocephala hybrid-Bahru during the initial period of feeding, but after this period, the fungi could have adapted to the CT and thrived, resulting in an enormous increase in fungal growth at day 15. However, the rapid growth was not sustained with prolonged exposure to CT of L. leucocephala hybrid-Bahru. Further studies using pure CT extracted from L. leucocephala hybrid-Bahru were then carried out to determine the effects of pure CT on the enzyme activities of some isolated cellulolytic rumen fungi. One hundred and twenty rumen fungi were isolated and identified to the genus level based on gross morphological characteristics. All the rumen fungal isolates identified belonged to two genera only, namely, Neocallimastix and Piromyces. Four highly cellulolytic fungal isolates were then selected based on their rate of degradation of ball-milled filter paper (one Neocallimastix and one Piromyces isolated from treatment goats at day 0, and one Neocallimastix and one Piromyces isolated from treatment goats at day 25). The four selected highly cellulolytic Neocallimastix and Piromyces isolates were further identified to species level using detailed morphological and molecular characteristics, such as sequence analysis of the 18S rRNA gene and ITS1 region. The two Neocallimastix isolates were identified as Neocallimastix frontalis (NGL 01 from day 0 and NGL 25 from day 25 of feeding, respectively) but the two Piromyces isolates could only be identified as Piromyces sp. (PGL 01 from day 0 and PGL 25 from day 25 of feeding, respectively). Enzyme assays were carried out to estimate the effects of pure CT on the cellulolytic enzyme activities and fermentation end products of the four isolated fungi. Four enzyme activities were studied. They were carboxymethylcellulase (CMCase), filter paperase (FPase), xylanase and β-glucosidase. The results showed that enzyme activities of cellulolytic rumen fungi isolated from goats fed L. leucocephala hybrid-Bahru at day 25 (N. frontalis NGL 25 and Piromyces sp. PGL 25), and had been exposed to CT in the rumen, were numerically or significantly more than those of cellulolytic rumen fungi isolated from goats not fed with L. leucocephala hybrid-Bahru (N. frontalis NGL 01 and Piromyces sp. PGL 01) at all levels of CT inclusion, which indicate greater tolerance of CT in cellulolytic rumen fungi isolated from goat fed L. leucocephala hybrid-Bahru at day 25 (N. frontalis NGL 25 and Piromyces sp. PGL 25). In conclusion, CT from L. leucocephala hybrid-Bahru could affect population and cellulolytic enzyme activities of anaerobic rumen fungi.